Towards an abolition of the child protection system in Spain? Structural limitations of residential care - Ortega Ortigoza, Daniel (2026)
This paper aims to critically analyze the child and adolescent protection system in Spain, with particular attention to the predominant use of residential care as an intervention measure. It begins with the observation that, despite its formally protective nature, this measure is controversial in the scientific literature due to the consequences of separating children from their families of origin. The research adopts a theoretical reflectivemethodology, based on reviewing and engaging with academic contributions and established abolitionist theses in international contexts. It also considers structural factors such as the economic and social vulnerability of the affected families, the strain on available resources, and the limited quality of socio-educational intervention. From an intersectional and decolonial perspective, the study examines the implications of these dynamics for the reproduction of inequalities and the potential for the development of institutional abuse practices. The main conclusion is that there is a need to thoroughly review the structures of the protection system, incorporating abolitionist approaches that prioritize strengthening families and reducing the use of residential care as the predominant measure of state intervention.